Tinjauan Maqāṣid Al-Sharī’ah terhadap Pemboikotan Produk Israel - Nurkholidah, Susi; Diono, Marzuki (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2024)
The conflict between Palestine and Israel has led to a boycott of pro-Israel products. Several countries, including Indonesia through MUI Fatwa No. 83 of 2023, promoted the boycott of products affiliated with Israel as a form of support for Palestine which has caused good and bad impacts, especially for companies associated with Israel, especially in the United States, so the issuance of this fatwa has encouraged Muslims to take a boycott stance with stronger conviction. That is why it is worth studying in the maqāṣid al-sharī’ah study. The type of research method used in this research is qualitative research. This research in collecting data uses the library research study method (Library research). The result of this research shows that the influence of MUI fatwa Number 83 of 2023 for Muslims on the boycott of pro-Israel products, especially in Indonesia, has a strong Sharia foundation because the Muslim community already knows that Israel's actions are colonialism against Palestine. While in the maqāṣid al-sharī’ah review, the boycott of pro-Israel products is to help fellow Muslims to realize the objectives of sharia to achieve the welfare of fellow Muslims and weaken the power of Islam's enemies.